Ethnic variations in sexual partnerships and mixing, and their association with STI diagnosis: findings from a cross-sectional biobehavioural survey of attendees of sexual health clinics across England. (17th August 2019) - Aicken, Catherine RH; Wayal, Sonali; Blomquist, Paula; Fabiane, Stella; Gerressu, Makeda; Hughes, Gwenda; Mercer, Catherine H
Abstract : Objectives: Ethnic differences in partnership types and sexual mixing patterns may contribute to elevated STI diagnosis rates among England's Black Caribbean (BC) population. We examined the differences between BC and White British/Irish (WBI) sexual health clinic (SHC) attendees' reported partnerships and sexual mixing, and whether these differences could explain ethnic inequalities in STI, focusing on attendees reporting only opposite-sex partners (past year). Methods: We surveyed attendees at 16 SHCs across England (May to September 2016), and linked their survey responses to routinely collected data on diagnoses of bacterial STI or trichomoniasis ±6 weeks of clinic attendance ('acute STI'). Behaviourally-heterosexual BC and WBI attendees (n=1790) reported details about their ≤3 most recent opposite-sex partners (past 3 months, n=2503). We compared BC and WBI attendees' reported partnerships and mixing, in gender-stratified analyses, and used multivariable logistic regression to examine whether they independently explained differences in acute STI. Results: We observed differences by ethnic group. BC women's partnerships were more likely than WBI women's partnerships to involve age-mixing (≥5 years age difference; 31.6% vs 25.5% partnerships, p=0.013); BC men's partnerships were more often 'uncommitted regular' (35.4% vs 20.7%) and less often casual (38.5% vs 53.1%) than WBI men's partnerships (p<0.001). Acute STI was higher among BC women than WBI women (OR: 2.29, 95% CI 1.24 to 4.21), with no difference among men. This difference was unaffected by partnerships and mixing: BC women compared with WBI women adjusted OR: 2.31 (95% CI 1.30 to 4.09) after adjusting for age and partner numbers; 2.15 (95% CI 1.07 to 4.31) after additionally adjusting for age-mixing, ethnic-mixing and recent partnership type(s). Conclusion: We found that differences in sexual partnerships and mixing do not appear to explain elevated risk of acute STI diagnosis among behaviourally-heterosexual BC women SHC attendees, but this may reflect the measures used. Better characterisation of 'high transmission networks' is needed, to improve our understanding of influences beyond the individual level, as part of endeavours to reduce population-level STI transmission.